THE FUNCTION OF SETTING IN DEVELOPING DRAMATIC TENSION IN D. M. LARSON'S “THE WAITING ROOM” - Amos Frans Abdial Tarigan; Palti Hansd Togi Maruhum Simanjuntak; Adika Indotua Nainggolan; Daniel Saputra Gurning; Samuel Tampubolon; David Togi Hutahaean (STKIP Subang, 2026)
This study aims to analyze the function of setting in developing dramatic tension in D. M. Larson's The Waiting Room. The study uses a qualitative descriptive method because the data are presented in the form of dialogues and stage directions found in the drama script. The analysis focuses on how the setting, including the waiting room itself and the changing atmosphere of the ceiling, contributes to the development of dramatic tension throughout the play. The data were collected by reading the script carefully, identifying descriptions related to setting, and interpreting their relationship with the characters' emotions and the progression of the story. The findings show that the setting in The Waiting Room is not only used as the physical background of the story but also functions as an active dramatic element. The mysterious waiting room creates uncertainty from the beginning of the play, while the changing light of the ceiling reflects the emotional condition of the characters and increases the dramatic tension. The setting also supports the gradual revelation of the characters' memories and leads the audience toward the climax of the story. Therefore, the study concludes that setting has an important role in building suspense, creating emotional atmosphere, and strengthening the overall dramatic effect of the play.